Survey and Distribution of Symbiotic Bacteria Nodules Rhizobium spp and Determine Its effectiveness in Nitrogen Fixation - et al., Asaad Abdullah Sfook (International Journal of Advanced Science and Technology, 2019)
The nitrogen importance to plant growth encouraged researchers to study it as plants limiting factor. Nitrogen fixation by life organism Rhizobium spp. is an important to increase growth and yield. The study aimed to determine the distribution and activity of bacteria symbiotic in legume growing at Thi-Qar province- southern Iraq. Field survey studied at six locations grew with legumes to know bacteria types. Two field experiments were studied, so the first was the effect of bacteria concentration on cowpeas growth. Three bacterial concentrations were studied. The second was bacteria concentration and nitrogen fertilizer effectiveness on alfalfa dry and fresh weight yield including 3 levels from both factors. Plant vegetative qualities and nodules number affected significantly by the bacterial concentrations. The alfalfa dry and fresh yields significantly were affected by bacterial concentration and nitrogen. The inoculation of seed before planting is important to increase legume growth and yield. The biological Nitrogen fixation is the most important procedure in agriculture to reduce using of amount Nitrogen fertilizers to crop because of amounts of Nitrogen fertilizers is losing by many processes, like (soil erosion, ammonia volatilization, Denitrification, leaching NO3, and immobilization process). Increasing density of inoculation is causing increasing by nitrogen fixation, height of plants number of leaves, dry matter, fresh material, productivity of legumes, dry matter and fresh increasing a significantly p α 0.05 to all plants in the study. The number of nodules raised with increasing density of inoculation a significantly (p α 0.05). The bacteria that were isolated from broad been roots was R. legumninosarum. In addition, R. melioti was isolated from the alfalfa roots and the other bacteria such as R. trifolli and Brady R. sp. was isolated from clover (trefoil) and cowpeas crops respectively.